Preschool children's Turkish language skills related to various variables (sample of Denizli) - (:unkn) unknown (My University, 2010)
The purpose of this research is to study 5 - 6 years old preschool children's Turkish language skills related to various variables (socioeconomic status, profession of fathers, working of mothers, education levels of parents, numbers of siblings, age of children and gender of children) in Denizli. The sample of the research consisted of 223 (114 boys and 109 girls) preschool children of 5 - 6 years old attending preschools education in the central region of Denizli city. A personal information form and language development subscale of Marmara developmental scale was used to collect data. According to the results, the gender, age of the children and the parents' working status did not lead to any significant differences as a function of language usage skills of children. However, educational levels of the parents, profession of the fathers, numbers of the siblings and socioeconomic status did present significant differences as a function of language usage skills of children. © 2010 Academic Journals.
Keywords: Family variables; Gender; Language skills; Preschool children; Socioeconomic status